Burden of chronic low back pain: Association with pain severity and prescription medication use in five large European countries. Issue 3 (26th November 2021) - Perrot, Serge; Doane, Michael J.; Jaffe, Dena H.; Dragon, Erika; Abraham, Lucy; Viktrup, Lars; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Conaghan, Philip G.
Abstract: Objective: This study assessed associations between severity of, and prescription medication use for, chronic low back pain (CLBP) and health‐related quality of life, health status, work productivity, and healthcare resource utilization. Methods: This cross‐sectional study utilized SF‐12, EQ‐5D‐5L, and work productivity and activity impairment (WPAI) questionnaires, and visits to healthcare providers among adults with self‐reported CLBP participating in the National Health and Wellness Survey in Germany, France, UK, Italy, and Spain. Respondents were stratified into four groups according to pain severity (mild or moderate/severe) and prescription medication use (Rx‐treated or Rx‐untreated). Differences between groups were estimated using generalized linear models controlling for sociodemographics and health characteristics. Results: Of 2086 respondents with CLBP, 683 had mild pain (276 Rx‐untreated, 407 Rx‐treated) and 1403 had moderate/severe pain (781 Rx‐untreated, 622 Rx‐treated). Respondents with moderate/severe pain had significantly worse health‐related quality of life (SF‐12v2 physical component summary), health status (EQ‐5D‐5L), and both absenteeism and presenteeism compared with those with mild pain, including Rx‐untreated (moderate/severe pain Rx‐untreated vs. mild pain Rx‐untreated, p  ≤ 0.05) and Rx‐treated (moderate/severe pain Rx‐treated vs. mild pain Rx‐treated, p  ≤ 0.05) groups. Significantly more visits to healthcare providers in the last 6 months were reported for moderate/severe pain compared with mild pain for Rx‐treated (least squares mean 13.01 vs. 10.93, p  = 0.012) but not Rx‐untreated (8.72 vs. 7.61, p  = 0.072) groups. Health‐related quality of life (SF‐12v2 physical component summary) and health status (EQ‐5D‐5L), as well as absenteeism and presenteeism, were significantly worse, and healthcare utilization was significantly higher, in the moderate/severe pain Rx‐treated group compared with all other groups (all p  ≤ 0.05). Conclusion: Greater severity of CLBP was associated with worse health‐related quality of life, health status, and absenteeism and presenteeism, irrespective of prescription medication use. Greater severity of CLBP was associated with increased healthcare utilization in prescription medication users.